Notice for additional work of waterproofing work for retain wall and capping beam - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the notice for additional work of waterproofing work for retain wall and capping beam of Brac University new campus development project.